Estudio del consumo horario residencial de agua potable en las redes Saboya; Veranillo; Maldonado; Piscin de la ciudad de Riobamba. - Alulema Roman, Leonardo Miguel (2023)
The Riobamba canton, located in the province of Chimborazo, is made up of 5 urban parishes and 11 rural parishes, thus having a total of 45,902 users, of which 80% belong to the residential sector, according to EP-EMAPAR, a service provider company. drinking water service, there are nine independent distribution networks that supply the entire city of Riobamba, injecting a flow of 680.26 l/s, however, it does not satisfy the demand that the city needs. The purpose of this research project is to analyze the behavior of hourly consumption of drinking water in the residential sector of the Saboya, Maldonado, San Martín de Veranillo and Piscín distribution networks based on statistical data and main parameters that influence water consumption. . For this, surveys were carried out in order to determine the number of dwellings that served as a study for data collection in the field. Regarding the processing and analysis of data, digital statistical tools were used that allowed the modeling curves and coefficients of variation of hourly consumption (kh) to be elaborated. The coefficients of greatest magnitude were in the Saboya and Maldonado network, values of 2.96 and 2. .99 respectively, which exceed the values recommended by the CPE INEN 5 1992 standard. These data are represented by georeferenced photogrammetry in order to distinguish the limits of each of the networks analyzed and help generate specific information for future designs in the networks. same.